ANALISIS ANTROPOLOGI-STRUKTURAL KISAH MUSA DAN KHIDZIR DALAM ALQUR’AN - M. Yaser Arafat (UIN Raden Mas Said Surakarta, 2018)
This study aims to examine the story of Moses and Khidzir as one of the Islamic narrative treasures in the Qur’an. Through Claude Lévi-Strauss’s structural-anthropology approach, to see the structure of mind that works in the story, the results showed that the story of Moses and Khidzir has a certain structure, which is appeared in the structure of non-ladunni and ladunni knowledge. The structure of knowledge can be seen from the existence of binary-opposition relation between Musa and Khidzir and the relation transformation in each episode of the story. Considering the structural-anthropology, the structure of the story must be identified in the human culture. Hereby, the ethnographic methods required to be used, in which the result revealed that the story of Moses and Khidzir believed as a code used by God to convey the general law of knowledge. The contribution of this study in the Qur’anic and socio-cultural studies is on the use of structural-anthropology approach, not only to analyze ‘parole’ and ‘langue’ of Qur’anic language but also to uncover the Qur’anic mind and identifying its existence in the human culture.